T2-Weighted Whole-Brain Intracranial Vessel Wall Imaging at 3 Tesla With Cerebrospinal Fluid Suppression - Zhang, Lei; Zhu, Yanjie; Qi, Yulong; Wan, Liwen; Ren, Lijie; Zhu, Yi; Zhang, Na; Liang, Dong; Li, Ye; Zheng, Hairong; Liu, Xin (Frontiers in Neuroscience, 2021)
Background: T2-weighted (T2w) intracranial vessel wall imaging provides good contrast to differentiate intracranial vasculopathies and discriminate various important plaque components. However, the strong cerebrospinal fluid (CSF) signal in T2w images interferes with depicting the intracranial vessel wall. In this study, we propose a T2-prepared sequence for whole-brain intracranial vessel wall imaging at 3T with CSF suppression. Methods: A preparation module that combines T2 preparation and inversion recovery (T2IR) was used to suppress the CSF signal and was incorporated into the commercial three-dimensional (3D) turbo spin echo sequence-Sampling Perfection with Application optimized Contrast using different flip angle Evolution (SPACE). This new technique (hereafter called T2IR-SPACE) was evaluated on nine healthy volunteers and compared with two other commonly used 3D T2-weighted sequences: T2w-SPACE and FLAIR-SPACE (FLAIR: fluid-attenuated inversion recovery). The signal-to-noise ratios (SNRs) of the vessel wall (VW) and CSF and contrast-to-noise ratios (CNRs) between them were measured and compared among these three T2-weighted sequences. Subjective wall visualization of the three T2-weighted sequences was scored blindly and independently by two radiologists using a 4-point scale followed by inter-rater reproducibility analysis. A pilot study of 4 stroke patients was performed to preliminarily evaluate the diagnostic value of this new sequence, which was compared with two conventional T2-weighted sequences. Results: T2IR-SPACE had the highest CNR (11.01 ± 6.75) compared with FLAIR-SPACE (4.49 ± 3.15; p<0.001) and T2w-SPACE (-56.16 ± 18.58; p<0.001). The subjective wall visualization score of T2IR-SPACE was higher than those of FLAIR-SPACE and T2w-SPACE (T2IR-SPACE: 2.52 35 ± 0.598; FLAIR-SPACE: 0.56 52 ± 0.541; T2w-SPACE: 1.6881 ± 0.5848); the two radiologists’ scores showed excellent agreement (ICC=0.883). Conclusion: The T2IR preparation module markedly suppressed the CSF signal without much SNR loss of the other tissues (i.e., vessel wall, white matter and gray matter) compared with the IR pulse. Our results suggest that T2IR-SPACE is a potential alternative T2-weighted sequence for assessing intracranial vascular diseases.